Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.stemcr.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Crypt Cell Remodeling Regenerates the Intestinal Stem Cell Niche after Notch Inhibition

Abstract: Summary Intestinal crypts have great capacity for repair and regeneration after intestinal stem cell (ISC) injury. Here, we define the cellular remodeling process resulting from ISC niche interruption by transient Notch pathway inhibition in adult mice. Although ISCs were retained, lineage tracing demonstrated a marked reduction in ISC function after Notch disruption. Surprisingly, Notch ligand-expressing Paneth cells were rapidly lost by apoptotic cell death. The ISC-Paneth cell changes were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 53 publications
3
24
1
Order By: Relevance
“…3). A recent study showed that acute Notch inhibition leads to rapid apoptosis of PCs, while Notch activation counteracts the death of PCs caused by caspase-8 (casp8) absence; these finding suggests that Notch signalling are required for PC maintenance [43,113].…”
Section: Growth Factor-mediated Signalling Pathways Regulate the Devementioning
confidence: 99%
See 1 more Smart Citation
“…3). A recent study showed that acute Notch inhibition leads to rapid apoptosis of PCs, while Notch activation counteracts the death of PCs caused by caspase-8 (casp8) absence; these finding suggests that Notch signalling are required for PC maintenance [43,113].…”
Section: Growth Factor-mediated Signalling Pathways Regulate the Devementioning
confidence: 99%
“…A subset of neuroD1-derived EECs can reserve stem cell properties in response to radiation-induced injury or under homeostatic conditions [42]. Upon intestinal injury, Dll1-and Dll4-expressing cells generate absorptive and secretory cells [43].…”
Section: Contribution Of Paneth Cells To Intestinal Epithelium Renewalmentioning
confidence: 99%
“… 6 Secretory precursors and differentiated Paneth cells have a modest but variable (0–50 lineage trace events per 5 cm) 17 contribution to epithelial regeneration that has been identified in multiple studies. 15 , 17 , 19 , 23 This reversion phenomenon appears dependent on Notch activation after DXR and IR. 17 , 18 , 19 …”
mentioning
confidence: 95%
“… 8 , 9 , 10 Recent studies demonstrate that Bmi1 marks cells of the enteroendocrine lineage. 11 Others have demonstrated the inherent plasticity of the intestinal epithelium, with varying degrees of regeneration originating from Dll1 + or Atoh1 + secretory progenitors, 12 , 13 , 14 , 15 differentiated Alpi1 + enterocyte precursors, 16 and differentiated Defa4 + , Lyz1 + , or Bhlha15 + Paneth cells. 17 , 18 , 19 …”
mentioning
confidence: 99%
“…Somewhat surprisingly, this triggers rapid apoptotic demise of Notch ligand-bearing Paneth cells, leaving Lgr5 + ISCs intact, albeit with diminished lineage-tracing capacity. Nevertheless, in this setting, both Lgr5 + ISCs (that activate expression of Dll1 ) and Dll1 + multipotent progenitors can mobilize to replenish the depleted Paneth cell pool and restore Notch homeostasis [ 141 ]. While these results contrast with the loss of Lgr5 + ISCs and the expansion of Paneth-like cells observed during prolonged Notch inhibition [ 84 ], they attest to the potential tolerability of transient Notch perturbation in the clinic and underscore that different modes of injury elicit distinct cellular and molecular responses.…”
Section: Niche Remodelling Post Injurymentioning
confidence: 99%